The prevalence of peri-implant disease following immediate implant placement and loading: a cross-sectional analysis after 2 to 10 years - Puria Parvini; Karina Obreja; Kathrin Becker; Maria Elisa Galarraga; Frank Schwarz; Ausra Ramanauskaite (International Journal of Implant Dentistry, 2020)
Abstract Background To evaluate the prevalence of peri-implant disease after immediate implant placement and loading. Material and methods This cross-sectional analysis included a total of 47 patients with 64 implants exhibiting a mean loading time of 2 to 10 years (4.23 ± 1.7 years). The surgical and prosthetic procedures were standardized in all patients. Peri-implant health and disease was assessed based on the established case definitions. Results The prevalence of peri-implant health, peri-implant mucositis, and peri-implantitis amounted to 38.3%, 57.5%, and 4.2% of the patients, respectively. Mucosal recession of 1 mm was present at 4 (6%) implants. No suppuration, pain, or implant failures were reported. Ordinal logistic regression revealed that reduced keratinized mucosa height was significantly associated with the diagnosis of peri-implant mucositis and peri-implantitis (OR = 0.514, P = 0.0125). Conclusion Immediate implant placement and loading was associated with high success rates at 2 to 10 years.